2001
DOI: 10.1097/00004872-200103001-00009
|View full text |Cite
|
Sign up to set email alerts
|

The release of the substrate for xanthine oxidase in hypertensive patients was suppressed by angiotensin converting enzyme inhibitors and α1-blockers

Abstract: It is concluded that the skeletal muscles of hypertensive patients released deltaHX in excess by activation of muscle-type adenosine monophosphate (AMP) deaminase, depending on the degree of hypoxia. The modification of deltaHX by angiotensin-converting enzyme inhibitors and alpha1-blockers influenced the level of serum uric acid, suggesting that the skeletal muscles may be an important source of uric acid as well as of the substrate of xanthine oxidase in hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 41 publications
3
23
0
Order By: Relevance
“…Small sample size may have contributed to the lack of statistical significance of some of the results, and did not allow us to perform multivariate analysis to detect factors responsible for the excess purine degradation. Second, number of control subjects was also small, but we would like to point out that control values for metabolites in this study were similar to those reported in our previous studies (9,13). Third, we acknowledge that the absence of clearance data for the metabolite is a limitation.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Small sample size may have contributed to the lack of statistical significance of some of the results, and did not allow us to perform multivariate analysis to detect factors responsible for the excess purine degradation. Second, number of control subjects was also small, but we would like to point out that control values for metabolites in this study were similar to those reported in our previous studies (9,13). Third, we acknowledge that the absence of clearance data for the metabolite is a limitation.…”
Section: Discussionmentioning
confidence: 50%
“…These findings suggest that HXis a good index of purine degradation through the purine nucleotide cycle, because the increased AMP deamination via activation of AMPdeaminase could accelerate the subsequent breakdown of inosine monophosphate to inosine, thereby leading to the increased formation of HX and Amm (1). Previous studies from our laboratory (9,13) showed that both HXand Ammlevels after forearm test increase in parallel. Thus, the augmented response in plasma HXto semi-handgrip exercise with the elevation of plasma Ammin the diabetic patients would reflect the activation of the purine nucleotide cycle in the exercising muscle.…”
Section: Discussionmentioning
confidence: 67%
“…Sur: serum uric acid, Uur: urinary uric acid, Scr: serum creatinine, Ucr: urinary creatinine, Uur/Ucr: urinary uric acid to urinary creatinine ratio, Cur/Ccr: urate clearance to creatinine clearance ratio, ARB angiotensin receptor blocker Irbesartan decreased Sur in both the group of patients where irbesartan was their fi rst angiotensin receptor blocker prescribed (fi rst group) and in the group of patients who were switched from another ARB (switch group), but did not affect Scr, Uur/Ucr, or Cur/Ucr in either group. genic hyperuricemia was caused by excessive degradation of the uric acid precursor hypoxanthine in skeletal muscles of hypertensive patients 7) . Losartan, one of the ARBs, has been reported to decrease Sur in hypertensive patients via inhibition of URAT1 20) , and several reports have shown that this property of losartan was abolished in hypertensive patients who carried a loss-offunction mutation in the URAT1 gene 21) .…”
Section: Discussionmentioning
confidence: 99%
“…The Guidelines for the Management of Hyperuricemia and Gout recommend the use of antihypertensive drugs that have favorable effects on uric acid metabolism, such as long-acting calcium channel blockers (CCBs), α-blockers, angiotensin-converting enzyme inhibitors (ACEIs), and angiotensin receptor blockers (ARBs), such as losartan 6) . CCBs, ACEIs, and α-blockers have been reported to suppress the production of the uric acid precursor hypoxanthine in skeletal muscles 7) . Losartan, specifically, has been reported to decrease Sur by enhancing urinary excretion of uric acid via inhibition of urate transporter 1 (URAT1) and glucose transporter 9 (GLUT9) 8) .…”
Section: Introductionmentioning
confidence: 99%
“…In these patients, an excess of hypoxantine, which is produced in the muscle during exercise, 2,39 has been suggested to be converted to urate by the enzyme xantine oxidase. 40 The enzyme catalyses, in a single reaction, not only the synthesis of urate, but also that of the superoxide radical. As a matter of fact, recent evidence suggests that hypertensive patients exhibit in plasma a significantly higher production of this free radical than control subjects.…”
Section: Discussionmentioning
confidence: 99%